The impact of the focus strategy on the achievement of fifth grade female students in science (Journal of the College of Basic Education, 2023)
The research aims to identify the impact of the focus strategy on the achievement of fifth grade female students in science, and to verify the objective of the research, the following null hypothesis was formulated:- There is no statistically significant difference at the level (0.05) between the mean scores of the experimental group students who will study according to the focus strategy and the mean scores of the control group who will study according to the usual method of achievement. The research community is represented by fifth-grade female students in Al-Izdihar Primary School for Girls, affiliated to the Baghdad Directorate of Education, Al-Rusafa, which was chosen intentionally, as they numbered (103) students distributed into three classes, and two groups were chosen by simple random assignment (lottery) (A, C) as a sample. For the research, (30) female students in each section after excluding the (9) female students who failed, and by simple random assignment, Division (C) represented the experimental group that studies according to the focus strategy, and Division (A) represents the control group that studies according to the method. the usual. The experimental design with partial control was chosen for the experimental and control groups with a post-test for the achievement of the fifth grade female students. The experiment was applied in the first semester of the academic year (2022_2023) and lasted (11) weeks. The content of the first three units, including the five chapters of the science book, was analyzed according to Bloom's classification of the cognitive field for levels (remembering, comprehension, application, analysis, synthesis), as it reached (164). behavioral goals, and (25) daily teaching plans were prepared for the experimental group according to the focus strategy, and the same for the control group according to the usual method. The students of the research sample (experimental and control) were rewarded in some of the variables that may affect the results of the research, namely (intelligence, previous information, and previous achievement). The researcher prepared the research tool, which is the achievement test, as it reached (26) objective items of the multiple choice type with four alternatives, and its apparent validity was verified by presenting it to the arbitrators and specialists in the methods of teaching science, measurement and evaluation, and the validity of (content) by preparing the test map (table Specifications), and its stability was calculated using the equation (Qodder-Richardson-20), as it reached (0.88), and the psychometric characteristics of the test items were extracted. After the completion of the application of the experiment, the achievement test was conducted on the students of the research sample (the experimental and control groups), and the data (research results) were analyzed statistically "depending on the statistical bag (spss), and the results showed the superiority of the students of the experimental group who studied using the focus strategy in the achievement test on their peers in the control group with a statistical significance and a significant effect on achievement. In the light of the research results, the researcher recommends using the strategy of concentration in teaching as an alternative to the usual method, and proposes a number of suggestions.